Antibody–drug conjugate: a newly developed biological missile for tumor treatment - Tang, Zhuoran; Xie, Yanchun; Zeng, Yanping (Frontiers in Oncology, 2025)
Antibody–drug conjugates (ADCs) represent one of the most advanced drug configurations under current research, primarily composed of a monoclonal antibody (mAb), a highly potent cytotoxic payload, and a linker that connects the drug to the antibody. The mAb serves mainly as a targeting moiety, guiding the conjugate to specific cells. The cytotoxic payload is responsible for the anticancer activity, whereas the linker ensures stable attachment between the antibody and the payload during circulation. The core advantage of ADCs lies in their ability to leverage the specificity of antibodies to deliver highly potent cytotoxic agents precisely to tumor cells, thereby significantly improving the therapeutic index. However, they also face challenges such as systemic toxicity, drug resistance, tumor heterogeneity, and complex manufacturing processes. Currently, extensive research is focused on technological innovations, the development of novel ADCs, and the optimization of clinical combination therapies. This article provides a comprehensive review of the structure and mechanism of action of ADCs, their developmental history, current challenges, emerging novel agents, and combination strategies with immune checkpoint inhibitors (ICIs).